(untitled) (Communications in Computational Physics, 2018)
Anion defect concentrations in the uranium dioxide were calculated in a wide temperature range by the molecular dynamics (MD) method, and a good agreement with the neutron scattering experimental data is shown. Groups of isolated interstitial anions with the absence of anion vacancies in N nearest neighborhoods (N=1−4) were extracted, formation energies of each group in the different phase states were derived. The formation energy of anion defects 4eV, derived by the MD method at low temperatures, in general coincides with the experimental estimations (3–4)eV and the lattice static results 4.1eV, using the same interaction potential. At high temperatures in the superionic state anion Frenkel defects (with N=3,4) have negative formation energy of about (-14)eV, concentrations of these defects are very small compared with the total defect concentration, including non-stoichiometric crystals. The validity of the point defects model in the superionic state and transition regions is also discussed. The model of anion diffusion via the formation of short-living pairs "vacancy-interstitial anion" is proposed and confirmed by MD calculations. It is shown that in the superionic state the exchange mechanism dominates, and at low temperatures it coexists with the diffusion via the formation of long-living anion Frenkel pairs.